2012 19th IEEE International Symposium on the Physical and Failure Analysis of Integrated Circuits 2012
DOI: 10.1109/ipfa.2012.6306307
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of laser ablation effects on Flash Memory devices

Abstract: It becomes a trend of replacing Au wire bonds with Cu wire bonds in the plastic IC packages due to the benefit of cost saving and electrical performance. Some plastic packages, such as FGBA package used for Flash Memory devices, utilize a new type of epoxy mold compound with higher reliability. Such mold compound is harder against chemical etching than other mold compounds and poses a greater challenge for failure analysis. The conventional manual acid dripping and automated acid etching do not work for the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Physical attack of the IC typically starts with partial or full removal of the chip As the application of laser ablation is increasingly used in IC package decapsulation process and offers many advantages, it will prompt the attackers to exploit this technique to access the die. Therefore it will be of great interest to study the It has been reported that when the laser strikes on the matter, the interaction between As mentioned in 2.5.4, the objective of laser decapsulation is to remove the package encapsulation by laser ablation and the most commonly used laser for the ablation/decapsulation of microelectronics packages is Nd-YAG laser [30]. In the next section, the reasons Nd-YAG laser being widely employed for this application by the market will be further elaborated.…”
Section: Decapsulation Methodologiesmentioning
confidence: 99%
“…Physical attack of the IC typically starts with partial or full removal of the chip As the application of laser ablation is increasingly used in IC package decapsulation process and offers many advantages, it will prompt the attackers to exploit this technique to access the die. Therefore it will be of great interest to study the It has been reported that when the laser strikes on the matter, the interaction between As mentioned in 2.5.4, the objective of laser decapsulation is to remove the package encapsulation by laser ablation and the most commonly used laser for the ablation/decapsulation of microelectronics packages is Nd-YAG laser [30]. In the next section, the reasons Nd-YAG laser being widely employed for this application by the market will be further elaborated.…”
Section: Decapsulation Methodologiesmentioning
confidence: 99%